Factors affecting 30-day mortality in poor-grade aneurysmal subarachnoid hemorrhage: a 10-year single-center experience - Scibilia, Antonino; Rustici, Arianna; Linari, Marta; Zenesini, Corrado; Belotti, Laura Maria Beatrice; Dall’Olio, Massimo; Princiotta, Ciro; Cuoci, Andrea; Aspide, Raffaele; Migliorino, Ernesto; Moneti, Manuel; Sturiale, Carmelo; et al. (Frontiers in Neurology, 2024)
Background The management of patients with poor-grade aneurysmal subarachnoid hemorrhage (aSAH) is burdened by an unfavorable prognosis even with aggressive treatment. The aim of the present study is to investigate the risk factors affecting 30-day mortality in poor-grade aSAH patients. Methods We performed a retrospective analysis of a prospectively collected database of poor-grade aSAH patients (World Federation of Neurosurgical Societies, WFNS, grades IV and V) treated at our institution from December 2010 to December 2020. For all variables, percentages of frequency distributions were analyzed. Contingency tables (Chi-squared test) were used to assess the association between categorical variables and outcomes in the univariable analysis. Multivariable analysis was performed by using the multiple logistic regression method to estimate the odds ratio (OR) for 30-day mortality. Results A total of 149 patients were included of which 32% had WFNS grade 4 and 68% had WFNS grade 5. The overall 1-month mortality rate was 21%. On univariable analysis, five variables were found to be associated with the likelihood of death, including intraventricular hemorrhage (IVH ≥ 50 mL, p = 0.005), the total amount of intraventricular and intraparenchymal hemorrhage (IVH + ICH ≥ 90 mL, p = 0.019), the IVH Ratio (IVH Ratio ≥ 40%, p = 0.003), posterior circulation aneurysms (p = 0.019), presence of spot sign on initial CT scan angiography (p = 0.015). Nonetheless, when the multivariable analysis was performed, only IVH Ratio (p = 0.005; OR 3.97), posterior circulation aneurysms (p = 0.008; OR 4.05) and spot sign (p = 0.022; OR 6.87) turned out to be independent predictors of 30-day mortality. Conclusion The risk of mortality in poor-grade aSAH remains considerable despite maximal treatment. Notwithstanding the limitations of a retrospective study, our report highlights some neuroradiological features that in the emergency setting, combined with leading clinical and anamnestic parameters, may support the multidisciplinary team in the difficult decision-making process and communication with family members from the earliest stages of poor-grade aSAH. Further prospective studies are warranted.